2003
DOI: 10.1111/j.1745-7599.2003.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Management of Sexually Transmitted Urethritis in Adolescent Males

Abstract: Young males with urethritis must be treated as soon as diagnosis is established. Consensus guidelines exist for diagnosis and treatment of gonococcal and non-gonococcal urethritis. Careful patient education is necessary to ensure successful treatment. Prevention of repeat infections requires partner treatment and detailed education about safer sexual practices. Improved access to preventive services for young males should be a healthcare priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Improved partner management is a high priority among heterosexual adolescents, 39,40 among whom the rates of gonorrhea and chlamydial infection in females outstrip those of all other age groups. 41 Recent data on partner notification in teens assessed dispositional correlates of success, such as self-efficacy and relationship quality.…”
Section: Special Populationsmentioning
confidence: 99%
“…Improved partner management is a high priority among heterosexual adolescents, 39,40 among whom the rates of gonorrhea and chlamydial infection in females outstrip those of all other age groups. 41 Recent data on partner notification in teens assessed dispositional correlates of success, such as self-efficacy and relationship quality.…”
Section: Special Populationsmentioning
confidence: 99%
“…Burning upon urination, penile discharge, urethral meatus erythema, pruritus, and stinging are "typical" manifestations of urethral sexually transmitted infections (STIs) in men. 1 In fact, urethritis is usually an STI in young men, 2 although 20-50% of male urethritis cases may have no identifiable infectious cause and are termed "non-specific urethritis". 3 We present here the case of a young man with typical STI manifestations yet a negative work-up for infections.…”
Section: Introductionmentioning
confidence: 99%
“…These infections affect both men and women; about 80% of infected women and 50% of infected men may be asymptomatic (2-4). These bacteria are also sexually transmitted, so it has been suggested that spermatozoa could be as vectors for transmission of these bacteria and cause female genital diseases and infertility (5).…”
Section: Introductionmentioning
confidence: 99%